2019
DOI: 10.1038/s41467-019-12420-1
|View full text |Cite
|
Sign up to set email alerts
|

3D extracellular matrix microenvironment in bioengineered tissue models of primary pediatric and adult brain tumors

Abstract: Dynamic alterations in the unique brain extracellular matrix (ECM) are involved in malignant brain tumors. Yet studies of brain ECM roles in tumor cell behavior have been difficult due to lack of access to the human brain. We present a tunable 3D bioengineered brain tissue platform by integrating microenvironmental cues of native brain-derived ECMs and live imaging to systematically evaluate patient-derived brain tumor responses. Using pediatric ependymoma and adult glioblastoma as examples, the 3D brain ECM-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 66 publications
1
73
0
Order By: Relevance
“…Limited capability for high-throughput screening applications Porous scaffolds [330][331][332][333][334][335][336][337][338][339][340][341][342]346,351,352,358] Long-term culture capability of larger scale tissue models Challenging to scale-up for high-throughput screening applications . This master pattern is then used as a mold for casting liquid PDMS, curing the polymer, and peeling the resultant replica with a negative relief from the master.…”
Section: Suitable For Noninvasive Imaging and Electrophysiological Rementioning
confidence: 99%
“…Limited capability for high-throughput screening applications Porous scaffolds [330][331][332][333][334][335][336][337][338][339][340][341][342]346,351,352,358] Long-term culture capability of larger scale tissue models Challenging to scale-up for high-throughput screening applications . This master pattern is then used as a mold for casting liquid PDMS, curing the polymer, and peeling the resultant replica with a negative relief from the master.…”
Section: Suitable For Noninvasive Imaging and Electrophysiological Rementioning
confidence: 99%
“…To address these issues, 3D cell culture models are a reliable alternative, providing experimentally accessible human models to study the biological processes of cancer. Several 3D culture platforms such as spheroids, organoids, hydrogels, 3D scaffolds, 3D bio-printing, and microfluidics have attempted the recreation of certain aspects of tumor microenvironments present in tissues including the brain [30][31][32][33][34][35][36], breast [37][38][39][40][41][42][43], ovarian [44][45][46][47][48][49][50][51], bone [52][53][54][55][56][57][58], liver [59][60][61][62][63][64][65], lung [66][67][68][69][70][71][72], colon [73][74][75][76]…”
Section: Mimicking Tme In Three-dimensionsmentioning
confidence: 99%
“…In the last decade, it has been demonstrated that non-invasive nonlinear microscopy represents a promising strategy for label-free live imaging of 3D engineered tissues. In fact, several studies had been performed to characterize morphology ( Hofemeier et al, 2016 ; Nguyen et al, 2017 ; Syverud et al, 2017 ; Costa Moura et al, 2018 ; Kaushik et al, 2019 ; Moura et al, 2019 ), functionality ( Hofemeier et al, 2016 ; Li et al, 2017 ; Syverud et al, 2017 ; Cong et al, 2019 ; Okkelman et al, 2020 ), composition and distribution of chemicals ( Hofemeier et al, 2016 ; Li et al, 2017 ; Syverud et al, 2017 ; Costa Moura et al, 2018 ; Moura et al, 2019 ; Sood et al, 2019 ), invasion, infiltration and mechano-regulation of cellular constructs ( Hofemeier et al, 2016 ; Nguyen et al, 2017 ; Syverud et al, 2017 ; Costa Moura et al, 2018 ; Kaushik et al, 2019 ; Moura et al, 2019 ; Sood et al, 2019 ), which have been collected in Table 4 . A representative study made by Hofemeier et al (2016) carried out a multi-spectral CARS and SHG imaging on an engineered bone tissue from stem cell differentiation toward osteogenic phenotype within 3 weeks of culture.…”
Section: Nonlinear Microscopy Toward 3d Bioengineered Systemsmentioning
confidence: 99%